Culture, Creativity and Tourism: A Study of Sikkim - Sattar, Sanjukta (National Geographical Journal of India, 2022)
Culture, creativity and tourism bear a symbiotic relationship as they mutually benefit each other. Culture in fact is one of important elements of tourism product which contributes to the uniqueness of the destination, adds to its attractiveness and gives the destination an identity of its own. On the other hand, tourism offers an important way for promoting, and preserving culture and cultural heritage and at the same time is functional in creating jobs and income as well as sustenance of the cultural heritage, cultural production and creativity. This communion of culture and tourism catalyse the flourishing of the creative potential of the host as well as the visitors. Just as tourism opens the avenues for the indigenous host population to sustainably nurture their cultural heritage and cultural skills through the practice of ’creative tourism’. This is ’creative tourism’ which is an activity that is meant for providing the tourists an authentic experience by giving them an opportunity to cultivate their creative talents throughtheir participative learning in the arts, heritage and culture of the destination. Against this background, an attempt has been made to examine the relationship between culture, creativity and tourism using evidences from Sikkim in this paper. The small Himalayan state of Sikkim since last twenty five years is one of the popular destinations among the tourists mainly because of its natural beauty although it is a storehouse of rich cultural heritage. The Sikkimese culture find expression in beautiful art and crafts , its rich tradition of performing arts and diverse eco-cultural heritage Recognition of the state’s rich heritage and culture and associating them with tourism activity will provide this destination with a different identity. This paper examines the prospect of ’Cultural and Creative Tourism’ in Sikkim